Pudicinae (Nematoda: Heligmonellidae) Parasitic in Endemic Chilean Rodents (Caviomorpha: Octodontidae and Abrocomidae): Description of a New Species and Emended Description of Pudica degusi (Babero and Cattan) n. comb. - Digiani, Maria Celina (2017)
We report the finding of 2 species of Pudica (Nematoda: Heligmonellidae: Pudicinae) in 2 rodents endemic to Chile, the common degu Octodon degus (Octodontidae) and the Bennett's chinchilla rat Abrocoma bennettii (Abrocomidae). Pudica degusi (Babero and Cattan, 1975) n. comb., originally described as a species of Longistriata (Heligmosomidae), was found in the common degu; through the study of its synlophe, the species is reassigned to the Heligmonellidae: Pudicinae and the genus Pudica, and it is revalidated through comparison with the remaining species of the genus. Pudica cattani n. sp. is described from both O. degus and A. bennettii. It is characterized by its large body size, bursal pattern of type 1-3-1 on right lobe, 1-3-1 tending to 1-4 on left lobe, synlophe with 11 ridges including a careen, dorsal ray of the bursa dividing proximally and bursal rays 9 and 10 relatively short. Pudica degusi n. comb. and Pudica cattani n. sp. were found in the same host species but not as coparasitic in the same individuals. The common degu is confirmed as the sole and primary host of Pudica degusi n. comb. It is unlikely that it is the primary host for Pudica cattani n. sp., whose host affinities are less clear mainly due to the scarcity of data. Pudica cattani n. sp. is the first helminth reported from the Bennett's chinchilla rat. Both findings enlarge the host range of the Pudicinae to the families Octodontidae and Abrocomidae, i.e., 9 out of the 11 extant families of caviomorphs, thereby establishing the presence of this nematode subfamily as typical parasites of the Neotropical Hystricognathi.